2019
DOI: 10.1002/path.5360
|View full text |Cite
|
Sign up to set email alerts
|

Clarin‐1 expression in adult mouse and human retina highlights a role of Müller glia in Usher syndrome

Abstract: Usher syndrome type 3 (USH3) is an autosomal recessively inherited disorder caused by mutations in the gene clarin-1 (CLRN1), leading to combined progressive hearing loss and retinal degeneration. The cellular distribution of CLRN1 in the retina remains uncertain, either because its expression levels are low or because its epitopes are masked. Indeed, in the adult mouse retina, Clrn1 mRNA is developmentally downregulated, detectable only by RT-PCR. In this study we used the highly sensitive RNAscope in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“… 99 However, several studies concluded that endogenous CLRN1 protein remains below the levels of detection of immunostaining. 47 , 49 , 97 , 100 Recently, we have generated and characterized a novel N-terminus epitope-tagged CLRN1 knock-in mouse to facilitate the detection of endogenous CLRN1 protein expression in retinal sections with a high affinity anti-HA antibody. 100 We noted a similar background labeling pattern in both HA-tagged CLRN1 knock-in and the C57BL/6J controls.…”
Section: Clrn1: An “Invisible” Tetraspanin Protein Of Unknown Biological Functionmentioning
confidence: 99%
See 1 more Smart Citation
“… 99 However, several studies concluded that endogenous CLRN1 protein remains below the levels of detection of immunostaining. 47 , 49 , 97 , 100 Recently, we have generated and characterized a novel N-terminus epitope-tagged CLRN1 knock-in mouse to facilitate the detection of endogenous CLRN1 protein expression in retinal sections with a high affinity anti-HA antibody. 100 We noted a similar background labeling pattern in both HA-tagged CLRN1 knock-in and the C57BL/6J controls.…”
Section: Clrn1: An “Invisible” Tetraspanin Protein Of Unknown Biological Functionmentioning
confidence: 99%
“… 47 , 49 , 97 , 100 Recently, we have generated and characterized a novel N-terminus epitope-tagged CLRN1 knock-in mouse to facilitate the detection of endogenous CLRN1 protein expression in retinal sections with a high affinity anti-HA antibody. 100 We noted a similar background labeling pattern in both HA-tagged CLRN1 knock-in and the C57BL/6J controls. Importantly, the HA-tagged CLRN1 in this mouse was only detectable by western blot analysis of retinal homogenates, and was expressed continuously during postnatal development and adulthood.…”
Section: Clrn1: An “Invisible” Tetraspanin Protein Of Unknown Biological Functionmentioning
confidence: 99%
“…Three genes underlying Usher 2 have been identi fied as USH2A (USH2A), 51 ADGRV1 (USH2C) 52 and WHRN (USH2D 65,66 Myosin VIIA is also an essen tial RPE protein, [67][68][69] and evidence suggests that clarin1 is restricted to the retinal Müller glia. 70 Various studies have indicated the involvement of Usher proteins in a range of processes, including cohesion, mechanotransduction, synaptic matu ration, and protein and organelle transport. 72,74,[88][89][90] However, missense mutations in CDH23 can also cause milder or 'atypical' Usher 1, and genotype-phe notype correlations are not always predictable.…”
Section: Genetics Of Usher Syndromementioning
confidence: 99%
“… 65 , 66 Myosin VIIA is also an essential RPE protein, 67 69 and evidence suggests that clarin-1 is restricted to the retinal Müller glia. 70 Various studies have indicated the involvement of Usher proteins in a range of processes, including cohesion, mechanotransduction, synaptic maturation, and protein and organelle transport.…”
Section: Genetics Of Usher Syndromementioning
confidence: 99%
“…In the retina, the protein is suggested to be localized in the inner segments and ribbon synapses of photoreceptors; however, recent data also suggest expression in Müller glia cells. 2 , 3 This gene encodes many different splice isoforms, whose function is also poorly understood. 4 CLRN1 mutations have an estimated prevalence of 1:100,000 individuals worldwide; however, USH3 is the major USH subtype in the Ashkenazi Jewish and the Finnish populations.…”
Section: Introductionmentioning
confidence: 99%